Human rights in the private sphere - "Clapham, Andrew" (Oxford, 1996)
The application of international human rights law to the private sphere has implications for the worlds of labor relations, race relations, discrimination and violence against women, and for victims of indignities everywhere. This study shows that respect for privacy need not mean excluding wrongs in the private sphere from the world of human rights. Concentrating on the rights contained in the European Convention on Human Rights, and their enforcement in the courts of the United Kingdom, it develops a coherent approach to human rights in the private sphere. In particular it challenges the presumption that the fundamental rights and freedoms contained in the European Convention on Human Rights are irrelevant for cases which concern the sphere of relations between individuals.
Keywords: Civil rights -Europe